Thinner [compact disc, unabridged] - Bachman, Richard (Penguin Audio, 2009)
When William Halleck accidentaly runs over an old gypsy woman, her father puts a deadly curse on him. Very overweight, he begins to lose about two pounds a day. As he becomes emaciated, he desperately searches for the gypsy who cursed him.